Spectral characterization of biphotons using quantum interferometric spectroscopy - Corona-Aquino, Samuel; Zeng, Zi-Qi; Xie, Tao; You, Shi-Xin; Ding, Chunling; Song, Yukun; Wang, Dongzhou; Meng, Yun; Zou, Kai; Hu, Xiaolong; Li, Baihong; U’Ren, Alfred B.; et al. (APL photonics, 2025)
The spectral distribution of photon pairs produced by spontaneous parametric downconversion (SPDC) is one of the most exploited degrees of freedom in multiphoton experiments. Consequently, the characterization of such correlations is, without a doubt, a task of utmost importance. Common methods for measuring the joint spectral intensity (JSI) of correlated photon pairs often exhibit several drawbacks, such as the requirement for a bright source to offset high losses or the need for two-dimensional measurements, which can lead to prolonged acquisition times. In this work, we experimentally demonstrate a technique that allows for the reconstruction of the JSI from a single interferometric measurement, thus reducing the dimensionality of the problem. The reconstructed JSIs show good agreement with those obtained directly through a fiber spectrometer, confirming the effectiveness of our approach. This technique significantly enhances the efficiency of JSI characterization, offering a resource-efficient method for quantum state characterization in SPDC-based experiments.